Analysis of the influence of pre-loading in the rating life calculation of tapered roller bearings applied to lightweight front-axle differentials - MacEdo, Gabriel Figlie [UNESP]; Nonato, Fábio (SAE International, 2012)
For intricate automotive systems that enclose several components, such as gearboxes, an important aspect of the design is defining the correct assembly parameters. A proper assembly can ensure optimized operating conditions and therefore the components can achieve a longer life. In the case of the support bearings applied to front-axle lightweight differentials, the assembly preload is a major aspect for an adequate performance of the system. During the design phase it is imperative to define reference values to this preload, so the application would endure its requirements. However, with the assistance of computer simulations, it is possible to determine an optimum condition of operation, i.e. optimum pre-load, which would increase the system reliability. This paper presents a study on the influence of preload on the rating life of tapered roller bearings applied to light-weight front axle differentials, evaluating how preload affects several key parameters such as rating life and displacement of components, taking into account the flexibility of the surrounding differential housing. Copyright © 2012 SAE International.
Keywords: Assembly parameters; Automotive Systems; Design phase; Key parameters; Light weight; Operating condition; Optimum conditions; Pre loads; Preloading; Reference values; Support bearings; System reliability; Tapered roller bearing; Computer simulation; Front axles; Rating; Roller bearings; Loading